How does organizational vigilance drive higher education performance? The mediating role of organizational ambidexterity - Irvianti, Laksmi Sito Dwi; Rahayu, Agus; Wibowo, Lili Adi; Sofia , Alfira (Indonesian Research Journal in Education |IRJE|, 2026)
This study examines the effect of organizational vigilance on higher education performance, with organizational ambidexterity as a mediating variable. The research was conducted in universities within the LLDIKTI III region of Indonesia, using a quantitative, cross-sectional survey design. Data were collected from 42 decision-makers at “Unggul”-accredited universities using structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that organizational vigilance has a positive and significant effect on organizational performance. Furthermore, organizational ambidexterity partially mediates the relationship between organizational vigilance and performance, suggesting that vigilance enhances performance both directly and indirectly through the organization’s ability to balance exploration and exploitation activities. These findings highlight the importance of strengthening environmental awareness and adaptive capabilities to improve university performance. Future research is recommended to use larger samples and additional variables to enhance generalizability.